The Mediating Role of Green Human Resource among the Relationship of Employees' Eco-friendly Attitude, Commitment, and Environmental Presentation - Muhammad Sajjad Hussain; Muhammad Arif Talha; Maryyam Karamat; Waseem Yousaf (iRASD Journal of Management)
The goal associated with this article is to explore the mediating role of green human resource management (GHRM) among the nexus of employees’ eco-friendly attitude, governmental commitment and environmental presentation in the textile industry of Pakistan. The employees that are related to the human resource department are the respondents who provide data with the help of questionnaires and analyzed this data with the help of PLS-SEM. The output of the existing literature shows that GHRM has positive mediation among the links of employees’ eco-friendly attitude, governmental commitment and environmental presentation in the textile industry of Pakistan. The upcoming studies along with the regulators will be the foremost users of the current study, and this study guides them while investigating this area in the future along with the development of the policies related to GHRM and environmental presentation.